Saving the Chinese Ghosts Overseas: A Study of the Yogacara Ulkā-mukha Ritual in Thailand - DU, Wenchen; LIU, Yaoping (International Conference on Law, Technology, Spirituality and Society (ICOLESS); Vol 4 (2024): The 7th International Conference on Law, Technology, Spirituality and Society (ICOLESS), 2024)
Currently, the most common methods of preserving spiritual practices related to supernatural beings from foreign lands involve conducting religious ceremonies and invoking nearby spiritual entities. This study aims to explore the spiritual significance and function of the Yogacara Ulkā-mukha ceremony in redeeming Chinese spirits residing abroad. The research design employs a phenomenological methodology, involving nine monks in Thailand as participants. Data were collected through in-depth interviews and participant observation, followed by thematic analysis to identify the challenges and deeper meanings associated with performing the ritual. The study reveals three key findings: first, the Yogacara Ulkā-mukha ritual embodies the concept of Buddhist compassion and the duty to rescue wandering souls seeking peace; second, it addresses the adaptation and challenges of maintaining tradition and cultural heritage in a modern context; and third, it highlights the power of intention and prayer in transcending spatial and temporal boundaries. These findings are further elaborated upon in the conclusion. Furthermore, the study suggests the development of a ritual adaptation model that incorporates technology to enhance the participation of overseas Chinese communities in preserving their spiritual traditions.